Population assessment and conservation status of Telmatobius macrostomus Peters, 1873 (Anura: Telmatobiidae) in high Andean wetlands, Pasco region (Peru) - Loza Del Carpio, Alfredo (2017)
Chinchaycocha lake frog, Telmatobius macrostomus Peters, 1873 (Anura: Telmatobiidae), is an endemic amphibian of the Central Andes Peru of very importance ecological and socioeconomic, whose population abundance is not known adequately and is categorized Endangered by the International Union for Conservation of Nature (IUCN) and by the Peruvian Legislation. Objectives were to assess your population in high Andean wetlands of the Pasco region and to do analysis of its threats and conservation status. For this, from October to December 2012, transects and quadrants were made on foot and snorkeling, doing intensive surveys in 65 places with habitats that included lagoons, rivers, streams, channels, water eyes and north of Chinchaycocha lake; population density was determined using Hayne estimator and appreciations were obtained from local residents through a survey. Presence of T. macrostomus was detected in only 10.76% of evaluated sites, being lagoons the main niche, varying its density from 0.65 to 3.01 individuals / ha, resulting very low values to ensure its population viability. The residents reaffirm that the species have a constant decrease, since 65% of people not observed the frog more than six years ago. Although there is a Supreme Decree in Peru which provides for its protection and the species is distributed into a protected area, these were insufficient measurements to guarantee its conservation, suggesting to implement other strategies and re categorize as Critically Endangered in Peruvian regulations.